Analisis Lukas 17:1-2 tentang Penyesatan dan Antisipasinya dalam Hidup Jemaat Masa Kini - Rusgiyati, Rusgiyati; Sumiwi, Asih Rachmani Endang (Angelion, 2023)
Misguidance among God's people is always there and this cannot be avoided by the congregation of God. This misguidance can be through teachings that are not based on the truth of God's Word and congregations that are influenced by deviant teachings because the congregation does not understand the truth of God's Word. This is a serious challenge for today's congregation, how every believer and leader of the congregation should behave and what anticipatory steps must be taken by leaders of the congregation and believers in dealing with misguidance. Through this article, the author provides an answer to the above, using a qualitative descriptive method by analyzing the text in Luke 17: 1-2, the results obtained are that misguidance is always there, the danger of misguidance especially for the weak, God's punishment for those who mislead and concern for the weak. The anticipation that is carried out is first, the congregation who continues to read and study the word of God will have their faith strengthened, not easily stumbled or carried away by bad things. Second, every leader of the congregation should equip the congregation with healthy teachings that are based on the truth of God's word and teach the correct doctrine.Penyesatan pada umat Tuhan selalu ada dan hal ini tidak bisa dihindari dialami oleh jemaat Tuhan. Penyesatan tersebut bisa melalui pengajaran yang tidak beralas pada kebenaran Firman Tuhan dan jemaat yang terpengaruh oleh pengajaran yang menyimpang karena kurang mengertinya jemaat akan kebenaran firman Tuhan. Ini menjadi tantangan serius bagi jemaat masa kini, bagaimana setiap orang percaya dan pemimpin umat harus bersikap dan langkah antisipasi apa yang harus diambil pemimpin umat maupun orang percaya dalam menghadapi penyesatan. Melalui artikel ini, penulis memberikan jawaban atas tersebut di atas, dengan menggunakan metode deskriptif kualitatif dengan menganalisis teks dalam Lukas 17:1-2 diperoleh hasil penyesatan memang selalu ada, bahaya penyesatan khususnya bagi orang-orang lemah, hukuman dari Allah bagi yang menyesatkan dan kepedulian bagi orang-orang lemah. Antisipasi yang dilakukan adalah pertama, jemaat terus membaca dan mempelajari firman Allah sehingga imannya akan semakin dikuatkan dan tidak mudah tersandung ataupun terbawa arus hal-hal yang tidak baik. Kedua, setiap pemimpin umat hendaknya membekali jemaat dengan pengajaran yang sehat yang berdasarkan kebenaran firman Tuhan dan mengajarkan doktrin yang benar